Analysis of Islamic business ethics and its impact during the Covid19 pandemic - Fajar Surya Ari Anggara; Roghiebah Jadwa Faradisi (University of Darussalam Gontor, 2020)
A good organization and business must have ethics and social responsibility according to its functions. By mapping the relationship patterns in such a business, it can be seen that the principles of business ethics are manifested in an interactive relationship pattern. The purpose of this paper is to analysis the Islamic business ethics perception in Ma’had Al-Muqoddasah Islam and its impact. In this study, the data qualitative approach used with employing interview methods as data collection technique. The findings of business ethics such as principles of autonomy, principles of honesty, principles of justice, principles of mutual benefit, principles of moral integrity related to Islamic values. Sincerity, simplicity, independence, ukhuwah Islamiyah and freedom are indicated as mahad five spirit that must attach on their employees. Impact to stakeholder’s perspective, especially parents of students have to follow dominant points to remember and adopt such as readiness, sincerity, trust to Allah, effort, and trust to institution. Ma’had Al-Muqoddasah strengthen Islamic business ethics and also enforcing all COVID-19 safety protocols.